2018
DOI: 10.4014/jmb.1801.01026
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glyphosate Resistance through Concurrent Mutations in Three Amino Acids of the Pantoea sp. 5-Enolpyruvylshikimate-3- Phosphate Synthase

Abstract: Glyphosate inhibits the target enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) in the shikimate pathway. A mutant of EPSPS from Pantoea sp. was identified using sitedirected mutagenesis. The mutant showed significantly improved glyphosate resistance. The mutant had mutations in three amino acids: Gly97 to Ala, Thr 98 to Ile, and Pro 102 to Ser. These mutation sites in Escherichia coli have been studied as significant active sites of glyphosate resistance. However, in our research, they were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Previously it has been shown that a mutation in EPSPS coding sequence can provide resistance to glyphosate, as demonstrated in goosegrass, Eleusine indica and Pantoea sp. [35,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been shown that a mutation in EPSPS coding sequence can provide resistance to glyphosate, as demonstrated in goosegrass, Eleusine indica and Pantoea sp. [35,43,44].…”
Section: Discussionmentioning
confidence: 99%